Establishing patterns in the formation of a fire-resistant sip panel with hemp insulation - Tsapko, Yuriy; Tsapko, Аleksii; Berdnyk, Oksana; Likhnyovskyi, Ruslan; Bielikova, Kseniia; Slutska, Oksana; Borysova, Anna; Lomaha, Vasyl; Uzhehova, Olha; Chaikovskiy, Vitalii (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the process that forms fire-resistant properties of SIP-panels with hemp insulation based on reactive coating and lime. The task addressed is to ensure the stability of SIP-panels and components when treated with coatings to changes in operating conditions. This is important since production from renewable sources for construction is a relevant issue. It has been proven that during thermal action on samples of hemp insulation treated with reactive coating and lime, no ignition and flame spread along the surface occurred. A layer of foam coke formed on the surface of the sample treated with reactive coating, which is 22 mm. The study has shown that when a burner is applied to a sample of SIP-panels with hemp insulation treated with reactive coating, after 110 s of thermal exposure, the process of forming a heat-insulating layer of coke began, which inhibited heat transfer. Instead, after the burner was exposed to a sample of SIP panels with hemp insulation treated with lime, a charring process occurred at the site of thermal action, but ignition and flame spread did not occur. Based on the results of determining the strength, it was found that treating the surface of hemp insulation with a coating increases the tensile strength by more than 2.5 times. Thus, increasing the amount of reactive coating on the surface of hemp insulation by half increases the tensile strength by 2.3 times. In the case of treating hemp insulation with lime, the tensile strength decreases by 3.4 times while increasing the amount of lime when treating the surface of hemp insulation to 0.38 kg/m2 increases the tensile strength by 5.3 times. Thus, there is reason to argue about the possibility to design effective and operationally stable biocomposites for construction.